Modulation of recombination zone position for quasi-two-dimensional blue perovskite light-emitting diodes with efficiency exceeding 5 - Li, Zhenchao; Chen, Ziming; Yang, Yongchao; Xue, Qifan; Yip, Hin-Lap; Cao, Yong (Nature communications, 2019)
In recent years, substantial progress has been made in developing perovskite light-emitting diodes with near-infrared, red and green emissions and over 20% external quantum efficiency. However, the development of perovskite light-emitting diodes with blue emission remains a great challenge, which retards further development of full-color displays and white-light illumination based on perovskite emissive materials. Here, firstly, through composition and dimensional engineering, we prepare quasi-two-dimensional perovskite thin films with improved blue emission, taking advantages of reduced trap density and enhanced photoluminescence quantum yield. Secondly, we find a vertically non-uniform distribution of perovskite crystals in the PEDOT:PSS/perovskite hybrid film. Through modulating the position of the recombination zone, we activate the majority of quasi-two-dimensional perovskite crystals, and thus demonstrate the most efficient blue perovskite light-emitting diode to date with emission peak at 480 nm, record luminance of 3780 cd m −2 and record external quantum efficiency of 5.7%. Halide perovskite based light-emitting diodes attracted intensive research interest recently but the efficiency of blue diodes is much lower than the green and red ones. Here Li et al. push up the efficiency of blue diodes through composition engineering and vertical morphology control.